Biosynthesis, bioactivity, biotoxicity and applications of antimicrobial peptides for human health - Daixu Wei; Xuwei Zhang (Elsevier, 2022)
Antimicrobial peptides (AMPs) are the natural antibiotics recognized for their broad-spectrum resistance to bacteria, fungi, viruses and parasites, and influencing the host immune responses. AMPs attributed to good biological effects have been used in various areas of human health, which are trying to completely replace antibiotics, owing to serious drug-resistance bacteria. However, limited bioactivity and potential biotoxicity of some AMPs was neglected, attributable to their hydrophobic structure with positive charges and nonspecific destruction of cell membranes. Various strategies have been used to design and biosynthetic optimized AMPs to improve their bioactivity, productivity, while lowering host toxicity and cost. Here, we focus on the progress made in understanding the AMPs, including biosynthesis (AMP-BioDesign 1.0 and 2.0), bioactivity (e.g. immune regulation and broad-spectrum or nonspecific actions against bacteria, viruses or parasites), and principle biotoxicity (e.g. hemolysis, acute toxicity and instability, ect). The application prospects of AMP for human health, clinical medicine (for novel drugs), tissue engineering and drug delivery system, respectively, are summarized in this review. Furthermore, future prospects and new strategy for the development of effective and low-toxic AMP formulations for human health are discussed.